Neoadjuvant treatment in ovarian cancer: New perspectives, new challenges - Nikolaidi, Adamantia; Fountzilas, Elena; Fostira, Florentia; Psyrri, Amanda; Gogas, Helen; Papadimitriou, Christos (Frontiers in Oncology, 2022)
Ovarian cancer remains the leading cause of death from gynecological cancer. Survival is significantly related to the stage of the disease at diagnosis. Of quite importance is primary cytoreductive surgery, having as a goal to remove all visible tumor tissue, and is the standard primary treatment in combination with platinum-based chemotherapy for patients with advanced ovarian carcinoma. Neo-adjuvant chemotherapy (NACT) has been implemented mostly in treating advanced disease, with studies performed having numerous limitations. Data extrapolated from these studies have not shown inferiority survival of NACT, compared to primary debulking surgery. The role of NACT is of particular interest because of the intrinsic mechanisms that are involved in the process, which can be proven as therapeutic approaches with enormous potential. NACT increases immune infiltration and programmed death ligand-1 (PDL-1) expression, induces local immune activation, and can potentiate the immunogenicity of immune-exclude high grade serous ovarian tumors, while the combination of NACT with bevacizumab, PARP inhibitors or immunotherapy remains to be evaluated. This article summarizes all available data on studies implementing NACT in the treatment of ovarian cancer, focusing on clinical outcomes and study limitations. High mortality rates observed among ovarian cancer patients necessitate the identification of more effective treatments, along with biomarkers that will aid treatment individualization